The Influence of Organization Culture, Job Satisfaction, and Work Involvement on Employees’ Organizational Commitment at Sorong Satte Polytechnic - Aji, Danyaka Putra; Ismail, Tubagus; Priyati, Rini Yayuk (Global Synthesis in Education Journal, 2025)
This study aims to investigate the impact of organizational culture and organizational commitment on employee performance, as measured by job satisfaction, at Sorong State Polytechnic. This study is quantitative. The population in this study was all employees at Sorong State Polytechnic. The sampling technique employed was a saturated sample, comprising 179 individuals. The data collection technique used a questionnaire that had been tested for validity and reliability. The data analysis technique used was SEM AMOS. The results of this study indicate that: (1) there is a positive influence of organizational culture on employee job satisfaction, (2) there is a positive influence of organizational commitment on employee job satisfaction, (3) there is a positive influence of organizational culture on employee performance, (4) there is a positive influence of organizational commitment on employee performance, (5) there is an influence of job satisfaction on employee performance.